2003
DOI: 10.1091/mbc.e02-09-0583
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Stimulates the Epithelial-to-Mesenchymal Transition of Human Colonic Organoids

Abstract: An epithelial-mesenchymal transition (EMT) characterizes the progression of many carcinomas and it is linked to the acquisition of an invasive phenotype. Given that the tumor microenvironment is an active participant in tumor progression, an important issue is whether a reactive stroma can modulate this process. Using a novel EMT model of colon carcinoma spheroids, we demonstrate that their transforming-growth factor-␤1 (TGF-␤)-induced EMT is accelerated dramatically by the presence of activated macrophages, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
255
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(272 citation statements)
references
References 46 publications
10
255
2
1
Order By: Relevance
“…Consistent with these findings in carcinoma tissues, decreased E-cadherin and cell proliferation, and increased SNAI2, laminin a3 and g2 chains, and MMP7 defined spontaneous EMT of the carcinoids. Thus, different variations of the LIM1863 cell line can model the complete EMT associated with single-cell dissociation from the tumour mass (Bates and Mercurio, 2003;Bates et al, 2005) as well as the initial stages of tubular de-construction (incomplete EMT) and construction (carcinoid assembly) as we show in the current study. Moreover, the LIM1863-Mph cells recapitulate the dynamic nature of these transitions.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Consistent with these findings in carcinoma tissues, decreased E-cadherin and cell proliferation, and increased SNAI2, laminin a3 and g2 chains, and MMP7 defined spontaneous EMT of the carcinoids. Thus, different variations of the LIM1863 cell line can model the complete EMT associated with single-cell dissociation from the tumour mass (Bates and Mercurio, 2003;Bates et al, 2005) as well as the initial stages of tubular de-construction (incomplete EMT) and construction (carcinoid assembly) as we show in the current study. Moreover, the LIM1863-Mph cells recapitulate the dynamic nature of these transitions.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, it has been known for some time that TGFb induces EMT in LIM1863 cells (Hayward et al, 1995). More recently, Bates and Mercurio (2003) have shown that tumour necrosis factor (TNF) a accelerates TGFb-mediated EMT, and that combined TGFb/TNFa treatment of LIM1863 cells is an excellent model of integrin modulation during CRC metastasis . This cytokine-induced EMT of LIM1863 cells described by Bates et al (2005) induces complete EMT, as defined by loss of E-cadherin expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase of TNF-α release brings about further NF-κB activation via TNFR1 signaling pathway in the cells and resultant elevation of MMPs secretion. As an autocrine TNF-α from tumor cells stimulated by this cytokine was reported (38), TNF-α release from the highly metastatic cells is possibly amplified in an autocrine mannaer. These findings suggest an autoactivation mechanism for TNF-α-triggered NF-κB activation in these cells.…”
Section: Discussionmentioning
confidence: 88%